Sequential Abiotic‐Biotic Processes Drive Organic Carbon Transformation in Peat Bogs. Issue 2 (25th February 2021) - Fudyma, Jane D.; Toyoda, Jason G.; Chu, Rosalie K.; Weitz, Karl K.; Heyman, Heino M.; Eder, Elizabeth; Hoyt, David W.; Gieschen, Hans; Graf Grachet, Nathalia; Wilson, Rachel M.; Tfaily, Malak M.
Abstract: Peatlands, which store one third of the terrestrial carbon (C), are subject to large disturbances under a changing climate. It is crucial to understand how microbial and physiochemical factors affect the vulnerability of these large C stores to predict climate‐induced greenhouse gas fluxes. Here, we used a combination of mass spectrometry and spectroscopy techniques, to understand sequential biotic and abiotic degradation pathways of Sphagnum fallax leachate in an anaerobic incubation experiment, in the presence and absence of microorganisms. Removal of microorganisms was carried out by passing aqueous samples through 0.2‐µm filters. Our results revealed that S. fallax leachate degradation by abiotic reactions is a significant contributor to CO2 production. Further, abiotic factors, such as low pH, are responsible for partial dissolved organic carbon (DOC) degradation that produces bioavailable compounds that shift microbial metabolic pathways and stimulate respiration in peat bogs. Acid‐catalyzed hydrolysis of Sphagnum ‐ produced glycosides can provide the microbial communities with glucose and stimulate microbial respiration of DOC to CO2 . These results, while unique to peatlands, demonstrate the importance and underscore the complexity of sequential abiotic and biotic processes on C cycling in peat bogs. It is therefore crucial to incorporate abiotic degradation and sequential below‐ground biotic and abiotic interactions into climate models for a better prediction of the influence of climate change on DOC stability in peatlands. These findings might not be representative of other ecosystems with different environmental conditions including mineral‐rich peatlands and plant matter in surface peat horizons that comprise discrete microbial populations, and DOC composition. Plain Language Summary: Peatlands store a large amount of carbon (C) in its soil that can be released into the air as CO2 . Microorganisms in peatland soil can utilize C and release it into the atmosphere. Abiotic influences (nonmicrobial), such as acidity, can also release C into the atmosphere by complete mineralization and/or by breaking it apart into simpler forms of C for microbial consumption. Here, we incubated dissolved organic carbon leachate from Sphagnum, a dominant vegetation in peatlands, for 70 days and removed microorganisms from one treatment. We found that with no microorganisms, carbon is being released to the air as CO2, and that without microorganisms more CO2 is being released overall. With microorganisms, C is being eaten and transformed differently by microorganisms before being released to the air, which only contributes to ∼10% of the CO2 released in our experiment. We also found that acidity could be cleaving larger forms of C to simpler forms, which these simple forms are more appealing to microorganisms to consume. Therefore, the importance of both abiotic (acidity) and biotic (microorganisms) influences on CO2 production from peatland soils should be considered when predicting ecosystem responses to climate change. Key Points: Abiotic reactions are a significant contributor to CO2 production in acidic peat bogs Acid‐catalyzed hydrolysis of complex molecules (e.g., glycosides) results in enhanced availability of glucose for microbial consumption in peat bogs Abiotic reactions shift microbial metabolic pathways and stimulate respiration in peat bogs